Estudio económico para la creación de una microempresa productora de carbón ecológico en base a la cáscara del coco en el recinto El Limonal, cantón Simón Bolívar, provincia del Guayas - Lema Bajaña, Lissette Lisbeth (2019)
This economic study considered the feasibility or feasibility of creating a micro company for the production and production of ecological - vegetable coal as raw material the coconut shell in a sector that is being neglected by the different governmental sectors such as El Limonal enclosure, Simón Bolívar canton, province of Guayas. The general objective was to determine through the economic study the creation of a micro-company that produces ecological coal based on the coconut shell in the El Limonal site, Simón Bolívar canton, province of Guayas. The methodology used was descriptive, field, bibliography, experimental, mixed (qualitative - quantitative); whose instruments were surveys directed at the residents of the El Limonal campus and a semi - structured interview with the most important actors in the sector……….